Industrial training report: Farm Fresh Klang Valley / Nur Haziqah Che Mat Bahri - Che Mat Bahri, Nur Haziqah (Universiti Teknologi MARA, Perlis, 2024)
to immerse myself in numerous areas of the marketing industry during my marketing internship at Farm Fresh Klang Valley, acquiring practical experience and honing crucial abilities. In addition to doing market research and evaluating consumer behavior data, I was actively involved in creating and implementing digital marketing strategies. In addition, I had to manage social media accounts, produce interesting content and help with the creation of marketing materials. I gained knowledge of the basics of brand positioning and target audience identification by working with the marketing team and participating in strategic planning sessions. My comprehension of marketing ideas has improved and this internship has sharpened my ability to apply them successfully in a fast-paced commercial setting. The report offers a thorough overview of my marketing internship experience and is divided into nine sections. The student’s profile which consists of my resume comes first. An summary of Farm Fresh, including its mission and basic values, can be found in the corporate profile section. The reflection portion of the program dives into my individual experiences and insights from the internship. To evaluate the opportunities, threats, weaknesses, and strengths faced, a SWOT analysis is provided. Based on my findings, the discussion and recommendation area offers ideas and insights. The report's main conclusions are outlined in a summary. Appendices contain additional materials supporting the primary content and references are given to acknowledge sources.